T-ABSO and strongly T-ABSO Fuzzy second submodules and Related Concepts - Wafaa H. Hanoon, Aseel S. Ibrahim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this search, we present the concepts T-ABSO fuzzy second submodules and strongly T-ABSO fuzzy second submodules, as well as some basic properties and characterizations of these concepts under the categories of multiplication fuzzy modules, cocyclic fuzzy modules, and comultiplication fuzzy modules. We also address the relationship among T-ABSO fuzzy second submodules, strongly T-ABSO fuzzy second submodules, and quasi T-ABSO fuzzy second submodules. Also, we study these concepts with other related fuzzy submodules.